Elements of knowledge management in the improvement of business processes = Elementy zarządzania wiedzą w doskonaleniu procesów biznesowych - Brajer-Marczak, Renata (Zielona Góra: Faculty of Economics and Management Press)
The key role in process management is played by the systematic analysis, measurement and improvement of processes. The imperative of continuous introduction of changes in processes is the answer to the changing conditions of competition and the great dynamics in the expectations and preferences of customers. Information related to business process should be collected and formalized in order to improve the execution of processes.
Keywords: zarządzanie wiedzą; zasoby wiedzy; proces biznesowy; doskonalenie; knowledge management; knowledge resources; business process; improvement of process